THE EFFECTIVENESS OF THE BUZZ GROUP DISCUSSION METHODS ON IMPROVING THE COLLABORATION OF BASIC SCHOOL STUDENTS - Ningsih, Berliana; Suryani, Ela (Sekolah tinggi ilmu ekonomi pemuda, 2021)
Abstract This study aims to determine the effectiveness of the Buzz Group discussion method on improving the collaboration ability of elementary school students. The research design was a quasi experiment, non equivalent control group design. The sample was taken by purposive sampling and obtained class V SD Negeri Muncar 01 as the experimental class and SD Negeri Muncar 02 as the control class. Data collection techniques using observation, tests, and documentation. The data analysis techniques in this study were normality test, homogeneity test, independent sample T-test, simple linear regression test, and paired sample T-test. The results showed: 1) There were differences in the use of the large group method and the buzz group discussion, this was evidenced by the independent sample T-test with a significance level of <0.05, namely 0.00 <0.05, 2) There was an influence on the use of the buzz discussion method. groups towards increasing the ability of student cooperation, this is evidenced by a simple linear regression test with a significance level of <0.05, namely 0.44 <0.05, and 3) There is an increase in students' cooperation abilities, this is evidenced by the paired sample T-test. Test with a significance level of <0.05, namely 0.00 <0.05 after using the buzz group discussion method. Keywords: Buzz group discussion, cooperation skills